Sequence and tectonostratigraphy of the Neoproterozoic (Tonian-Cryogenian) Amundsen Basin prior to supercontinent (Rodinia) breakup - Thomson, D.; Rainbird, R.; Krapez, Bryan (Elsevier, 2014)
Intracontinental basins that lack obvious compartmentalization and extensional faults may lie inboard of, and have the same timing as, rifted continental margins. Neoproterozoic successions of northwest Laurentia are an example where rift and intracontinental basins are spatially and temporally related. This study describes Tonian-Cryogenian pre-rift strata of the upper Shaler Supergroup, deposited in the Amundsen Basin (Victoria Island, Canada), in which five transgressive-regressive (T-R) cycles are identified. The pre-breakup succession in the Amundsen Basin has stratigraphic architecture that differs from adjacent, fault-bound rift basins. There is little evidence for extensive progradation, which resulted in broad, layer-cake stratigraphy where shallow-water facies predominate, deposited on a storm-dominated ramp. Correlation between the Amundsen and Fifteenmile (Yukon) basins is complicated by differing rates and regimes of subsidence, with the exception of a basin-deepening event that occurred in both basins and correlates with the global Bitter Springs isotope stage, initiating sometime after ~811 Ma. Contrary to previous correlations, we propose that the upper Shaler Supergroup and Little Dal Group of the Mackenzie Mountains Supergroup (Mackenzie Basin) are equivalent to the entire Fifteenmile Group. The identification of cycles and subsidence patterns in the Amundsen Basin prior to Rodinia break-up has implications for understanding the stratigraphic architecture of other intracontinental sag basins. We recognize three tectonostratigraphic units for the upper Shaler Supergroup that record an initial sag basin, followed by early extension and thermal doming, and finally rifting of the Amundsen Basin. Subsidence possibly was related to multiple cycles of intra-plate extension that complemented coeval fault-controlled subsidence. Analysis of pre-rift strata in the Amundsen Basin supports multi-phase, non-correlative break-up of Rodinia along the northwest margin of Laurentia.